Fungsi Dewan Keamanan PBB Dalam Penyelesaian Konflik Bersenjata Internasional - Maryam Marasabessy; Irma Halimah Hanafi; Josiana Agusthina Yvonne Wattimena (Faculty of Law Pattimura University, 2023)
Introduction: This study discusses the function of the UN Security Council in resolving international armed conflicts which have a very large role in fighting for and providing maintenance of world peace and security. The UN Security Council has a very large role in being a peacekeeper to stabilize conflicts related to information such as human rights, disarmament, gender, humanitarian relations and political affairs. The implementation of international law provisions in the UN Charter has not been carried out optimally because there are still countries that do not comply with the rules that have been set. Purposes of the Research: This study aims to identify and examine the functions of the Security Council in the structure of the UN international organization and to identify and examine the functions of the UN Security Council in resolving international conflicts according to the UN charter.Methods of the Research: The research method used is normative juridical research. This research is called library research because normative juridical research is carried out by examining sources of legal material using a law approach and a case approach. The use of legal material sources consists of primary, secondary and tertiary legal materials. The technique of collecting this research was done through library technique.Results of the Research: The United Nations Security Council as one of the main organs in the United Nations has functions and powers which are generally regulated in Articles 24 to 26 of the United Nations Charter which includes members of the United Nations giving the Security Council the main responsibility for maintaining international peace and security as well as having the responsibility in formulating plans to be submitted to members of the United Nations for the establishment of a system of arms regulation. In the conflict in Central Africa, the implementation of these provisions has not been carried out optimally because there are still violations by several parties by not complying with the policies issued by the Security Council. It requires the commitment of all disputing parties to comply with the applicable provisions of Humanitarian Law and provide strict sanctions against those who violate them.